The Relationship between government expenditure on education and fertility in Sub – Saharan Africa - Mwangi, Susan Wanjiku (Strathmore University, 2021)
This dissertation estimates the changes in fertility rates in SSA, achieved by targeting government expenditure on education towards women’s education. Additional determinants of fertility were included in the model to ascertain the predictive validity and significance of government expenditure on education. They include the contraceptive prevalence, female unemployment rate, gross national income per capita, infant mortality rate, male employment rate, urbanization growth rate, and the Tax to GDP ratio. The theoretical foundation for this dissertation is the Theory of Increasing Prosperity, Theory of Human Capital and Wagner’s Law of Increasing State Activities. Panel Data spanning 1980 – 2017 of a sample of twenty – one countries was coded into a series of simultaneous equations executed through a Structural Equation Modelling tool. The results reveal a positive and significant correlation between government expenditure on education and the female school enrollment rate. Additionally, the findings show a significant and negative relationship between government expenditure on education and fertility. More importantly, the magnitude of this effect intensifies with women’s education as a mediator. Furthermore, the aforementioned relationships remain significant in the presence of other determinants of fertility. This dissertation concludes that government expenditure has the potential to achieve a reduction in fertility as an outcome, and specifically through women’s education, resulting from the benefits of Human Capital.
A dissertation submitted to Strathmore Business School in Partial fulfillment of the requirements for the award of Master of Science in Development Finance Degree of Strathmore University
Keywords: Government Expenditure Education; Fertility; School Enrollment; Structural Equation Modelling; Women’s Education